The Kenyan dairy and poultry sectors to benefit from a new research initiative - Kimani, Judy (International Livestock Research Institute, 2022)
Co-creation, with stakeholders, of the SAPLING vision and theory of change for the dairy cattle and poultry value chains in Kenya